Cost And Utilization Analysis In Increasing Cost Recovery Rate (CRR) In Rsu Royal Prima Medan 2022 - Franks Wijaya; Ermi Girsang; Tan Suyono (CV. Inara, 2023)
Cost Recovery Rateat the Royal Prima Medan Hospital, there was a surplus every year below 5% and even decreased in 2018 to less than 100%. The CRR surplus is still below 5% and the CRR decline is related to costs, tariffs and utilization. This study aims to analyze tariffs, costs and utilization in increasing the Cost Recovery Rate (CRR) at RSU Royal Prima Medan. This type of research is quantitative and qualitative research is descriptive analytic. The population and sample were the Director, Director of Medical Services, Head of Finance Subdivision, Head of Accounting and Marketing Subdivision at RSU Royal Prima Medan, totaling 5 informants. Data collection with primary and secondary data and data analyzed by data reduction, data display and data verification. The results of the study show that there is a change in the Cost Recovery Rate (CRR) every year, how to determine service product rates at RSU Royal Prima Medan and compare them to rates at competing hospitals in Medan, the number of sick people totaling 4222 people was only about 53 people who came out dead for various reasons, not because of the disease they suffered when they entered and the strategy carried out by RSU Royal Prima Medan in increasing CRR is to carry out promotions for several superior service products. It is recommended that because this research is limited to using only quantitative descriptive methods with a qualitative approach, the authors suggest that the leadership can re-examine the success of this research by opening other researchers using different methodologies and employees need to increase motivation and quality of service from year to year so as to make RSU Royal Prima Medan is indeed a hope for the wider community.